2020
DOI: 10.1136/bmjopen-2019-033446
|View full text |Cite
|
Sign up to set email alerts
|

Study protocol for efficacy and safety of steroid-containing mouthwash to prevent chemotherapy-induced stomatitis in women with breast cancer: a multicentre, open-label, randomised phase 2 study

Abstract: IntroductionStomatitis is a frequent adverse event in patients undergoing chemotherapy for breast cancer. Stomatitis can hamper oral nutrition resulting in malnutrition, reduce quality of life and introduce the need for dose reductions and interruption of chemotherapy; however, there is currently no standard approach for preventing chemotherapy-induced stomatitis. We aimed to assess the safety and efficacy of a dexamethasone-based elixir mouthwash for preventing chemotherapy-induced stomatitis in patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“… 72 Stomatitis, especially the grade 3 or 4 mucositis, 73 can hamper oral nutrition, resulting in malnutrition, reduce QoL and introduce the need for dose reductions and interruption of chemotherapy. 74 MLT has potential direct antitumour activity and has been proven to modulate the effects of cancer chemotherapy by enhancing therapeutic efficacy and reducing toxicity. 75 Our review showed that MLT had no effect on mucositis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 72 Stomatitis, especially the grade 3 or 4 mucositis, 73 can hamper oral nutrition, resulting in malnutrition, reduce QoL and introduce the need for dose reductions and interruption of chemotherapy. 74 MLT has potential direct antitumour activity and has been proven to modulate the effects of cancer chemotherapy by enhancing therapeutic efficacy and reducing toxicity. 75 Our review showed that MLT had no effect on mucositis.…”
Section: Discussionmentioning
confidence: 99%
“…Oral mucositis refers to inflammation and ulceration of the oral mucosa, which is a frequent side effect of cancer therapy 72. Stomatitis, especially the grade 3 or 4 mucositis,73 can hamper oral nutrition, resulting in malnutrition, reduce QoL and introduce the need for dose reductions and interruption of chemotherapy 74. MLT has potential direct antitumour activity and has been proven to modulate the effects of cancer chemotherapy by enhancing therapeutic efficacy and reducing toxicity 75.…”
Section: Discussionmentioning
confidence: 99%